Phylogeny and biogeography of some Cretaceous spatangoid echinoids with special emphasis on taxa from the Western Interior Seaway. (May 2021) - Byrum, Steven; Lieberman, Bruce S.
Abstract: Members of the echinoid order Spatangoida, a highly diverse and abundant marine invertebrate clade, were important denizens of the Cretaceous Western Interior Seaway (WIS), an epicontinental seaway that divided North America in two during an interval of greenhouse conditions between roughly 100 and 65 million years ago. A phylogenetic analysis of spatangoids was conducted using a character matrix of 32 characters from 21 species. Species that occur in the WIS were considered comprehensively, and species from other regions such as South America, Europe, and North Africa were also incorporated into the analysis. Phylogenetic patterns retrieved are largely congruent with preexisting family-level classifications; however, species within several genera, especially Hemiaster and Heteraster, need to be reassigned so that classification better reflects phylogeny. The genera Washitaster and Heteraster are closely related, as are Mecaster, Palhemiaster, and Proraster ; Pliotoxaster, Macraster, and Hemiaster ; and Micraster and Diplodetus . Biogeographic patterns were also considered using the phylogeny, and several episodes of vicariance and range expansion were identified. These were possibly related to some of the various major episodes of sea-level rise and fall during the Cretaceous. In particular, Valangian–mid-Aptian regressions may have caused vicariance within Heteraster and Washitaster while other early spatangoid vicariance may be related to regressions during the late Aptian–early Cenomanian. Further, vicariance caused by regressions during the mid-Cenomanian–Maastrichtian may have driven diversification within Micraster and Diplodetus . Last, transgressions during the late Aptian–early Cenomanian seem to have spurred prominent range expansions in Mecaster and Hemiaster .